Shorter But More Frequent Rest Periods: No Effect on Velocity and Power Compared to Traditional Sets Not Performed to Failure - Jukic, Ivan; Tufano, James J (Journal of human kinetics, 2019)
Performing traditional sets to failure is fatiguing, but redistributing total rest time to create short frequent sets lessens the fatigue. Since performing traditional sets to failure is not always warranted, we compared the effects of not-to-failure traditional sets and rest redistribution during free-weight back squats in twenty-six strength-trained men (28 ± 5.44 y; 84.6 ± 10.5 kg, 1RM-to-body-mass ratio of 1.82 ± 0.33). They performed three sets of ten repetitions with 4 min inter-set rest (TS) and five sets of six repetitions with 2 min inter-set rest (RR6) at 70% of one repetition maximum. Mean velocity (p > 0.05; d = 0.10 (-0.35, 0.56)) and mean power (p > 0.05; d = 0.19 (-0.27, 0.64)) were not different between protocols, but the rating of perceived exertion (RPE) was less during RR6 (p < 0.05; d = 0.93 (0.44, 1.40)). Also, mean velocity and power output decreased (RR6: 14.10% and 10.95%; TS: 17.10% and 15.85%, respectively) from the first repetition to the last, but the percentage decrease was similar (velocity: p > 0.05; d = 0.16 (0.30, 0.62); power: p > 0.05; d = 0.22 (-0.24, 0.68)). These data suggest that traditional sets and rest redistribution maintain velocity and power output to a similar degree when traditional sets are not performed to failure. However, rest redistribution might be advantageous as RR6 displayed a lower RPE.
Keywords: cluster sets; power output; training effort; velocity; rest redistribution; resistance training